Diskursus Kajian Al-Qur’an dalam Kesarjanaan Barat: Sejarah, Tipologi, dan Implikasi Epistemologis - Rosnaeni Rosnaeni; Maharani Wulandari (Yayasan Cendekia Gagayunan Indonesia, 2025)
Qur’anic studies within Western scholarship have undergone significant development in terms of both methodological approaches and epistemological orientations. This article aims to examine the historical dynamics of Qur’anic studies in the West while mapping the principal typologies of orientalist approaches to the Qur’an. Unlike previous studies that are largerly descriptive in nature, this article emphasizes an analysis of the epistemological implications of orientalist scholarship, particularly in relation to the paradigm shift from polemical classical Orientalism to more academic and dialogical contemporary scholarship. This study employs library research using a historical-intellectual approach and discourse analysis. The findings indicate that Western Qur’anic scholarship is not monolithic but instead reflects a broad spectrum of approaches, ranging from historical criticism to literary and hermeneutical perspectives. Therefore, orientalist scholarship should be positioned in a critical and proportional manner as part of the global academic discourse on Qur’anic studies.